GROUP COUNSELING SERVICES WITH BEHAVIORAL REHEARSAL TECHNIQUES TO OVERCOME SOCIAL ANXIETY IN STUDENTS - Jannati, Zhila; Utami Fitri, Hartika; Anjlia, Dia (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Social anxiety is an excessive fear of negative evaluation from others, resulting in avoidance and discomfort in social interactions. Therefore, efforts are needed to overcome the problem of social anxiety, through group counseling services using behavioral rehearsal techniques. This research aims to determine the description of social anxiety in students of the 2024 Islamic Counseling Guidance (BPI) study program, the application of group counseling services using behavioral rehearsal techniques, as well as the condition of social anxiety after the service is provided. This research is descriptive in nature with a qualitative approach, using interviews, observation and documentation as data collection tools. The research subjects were five students from the BPI study program. Data analysis techniques include data reduction, data presentation, and conclusions. The research results show that students' social anxiety is characterized by fear of negative evaluation, social avoidance, and discomfort in social situations. Group counseling using behavioral rehearsal techniques helps students identify the causes of anxiety and train courage through behavioral exercises and feedback. After counseling, there was a decrease in social anxiety, increased courage, and comfort in social interactions.